Management der postoperativen Pankreasfistel = Management of postoperative pancreatic fistula - Hackert, Thilo; Büchler, Markus W. (Der Chirurg, 2015)
The occurrence of a postoperative pancreatic fistula is one of the most important complications following pancreatic resections. The frequency of this complication varies between 3 % after pancreatic head resection and up to 35 % following distal pancreatectomy. In 2005, the international definition of postoperative pancreatic fistula was standardized according to the approach of the International Study Group of Pancreatic Surgery (ISGPS) including an A-C grading system of the severity. Consequently, results from different studies have become comparable and the historically reported fistula rates can be evaluated more critically. The present review summarises the currently available data on incidence, risk factors, fistula-associated complications and management of postoperative pancreatic fistula.